Lead-carbon battery electrode preparation method, positive electrode plate, temperature control method and lead-carbon battery
By using MOFs-derived porous carbon to load lead nanoparticles in lead-carbon batteries, constructing a self-healing layer and modifying the positive electrode active material PbO2, combined with an intelligent temperature control method, the problems of weak interface bonding, agglomeration, insufficient self-healing ability and unreasonable temperature control of lead-carbon batteries were solved, and the battery performance and life were improved.
Patent Information
- Application Number
- CN202510857869.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-25
- Publication Date
- 2025-10-03
AI Technical Summary
In practical applications, lead-carbon batteries face problems such as weak interface bonding of electrode materials, agglomeration of lead nanoparticles, insufficient electrode self-repair ability, limited performance optimization of positive electrode active materials, and unreasonable battery temperature control, which lead to limited charging and discharging performance and service life.
By preparing MOFs-derived porous carbon-loaded lead nanoparticles, constructing a self-healing layer and modifying the positive electrode active material PbO2, combined with an intelligent temperature control method, the interfacial bonding force is enhanced, agglomeration is inhibited, the positive electrode performance is optimized, and precise temperature regulation is achieved.
It improves the battery's charge and discharge performance and cycle life, increases the utilization rate of active materials, extends the battery's service life, and ensures that the battery operates within the optimal temperature range, thereby improving the battery's safety and performance.
Smart Images

Figure CN120749128A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of energy storage batteries, and in particular to a lead-carbon battery electrode preparation method, a positive electrode plate structure, a battery temperature control method, and a corresponding temperature-controlled lead-carbon battery. Background Art
[0002] Lead-carbon batteries, as an important energy storage battery, improve their cycle life and power performance by introducing carbon materials into the negative electrode. Among the various carbon materials, MOFs-derived porous carbon has attracted widespread attention due to its high specific surface area and tunable pore structure.
[0003] There are many challenges in practical applications: Electrode material interface issues: Traditionally prepared carbon materials exhibit weak interfacial bonding with lead active materials, resulting in uneven lead deposition on the electrode surface. This not only triggers sulfation, increasing the battery's internal resistance, but can also cause electrode structural collapse, severely impacting the battery's charge-discharge performance and service life.
[0004] Nanoparticle agglomeration problem: During the charging and discharging process, lead nanoparticles will agglomerate due to the Ostwald ripening effect, resulting in a reduction in the number of active sites, a decrease in the utilization rate of active substances, and accelerated battery capacity decay, which cannot meet the needs of long-term stable power supply.
[0005] Insufficient electrode self-repair ability: The carbon-lead interface has poor stability during battery cycling and is prone to breakage. It also lacks an effective self-repair mechanism, causing battery performance to decline rapidly with increasing cycle times, limiting the widespread application of lead-carbon batteries.
[0006] Problems with modification of positive electrode active materials: There are limited means to optimize the performance of the positive electrode active material PbO2, and its synergistic effect with other materials has not been fully exerted, affecting the overall charge and discharge efficiency and energy density of the battery.
[0007] Improper battery temperature control: Existing battery temperature control systems offer a crude approach to temperature regulation, relying primarily on passive heat dissipation or simple heating to maintain temperature. These systems are unable to dynamically and accurately adjust the temperature based on the complex electrochemical reactions within the battery and the demands of electrode material self-repair. This results in the battery often operating at suboptimal temperatures, impacting performance, safety, and service life. Summary of the Invention
[0008] The present invention aims to solve the following key technical problems: Strengthen the interfacial bonding force between carbon materials and lead active substances, achieve uniform deposition of lead on the electrode surface, avoid sulfation and structural collapse problems, and improve battery charging and discharging performance and service life.
[0009] Inhibit the agglomeration of lead nanoparticles during the charging and discharging process, increase the number of active sites, improve the utilization rate of active materials, and slow down the rate of battery capacity decay.
[0010] An effective self-repairing layer is constructed on the electrode surface to enhance the stability of the carbon-lead interface during battery cycling. When the interface is damaged, it can automatically repair itself, thereby extending the battery life.
[0011] The positive electrode active material PbO2 is modified with suitable materials to optimize its performance and make it work well with other materials to improve the overall charge and discharge efficiency and energy density of the battery.
[0012] Design an intelligent and precise battery temperature control method that can dynamically adjust the battery temperature according to the internal reaction heat of the battery and the self-repair requirements of the electrode material, ensuring that the battery always operates within the optimal temperature range, thereby improving battery performance, safety and service life.
[0013] In order to solve the above technical problems, the present invention provides a method for preparing a lead-carbon battery electrode, comprising the following steps: Step 1: Precursor preparation: dissolving zinc nitrate in methanol and stirring magnetically until completely dissolved; dissolving 2-methylimidazole in methanol and stirring until dissolved; pouring the zinc nitrate solution into the 2-methylimidazole solution, stirring and reacting at room temperature; after the reaction is completed, collecting the white precipitate by centrifugation, washing, and vacuum drying to obtain ZIF-8 powder; Step 2: carbonizing the ZIF-8 powder obtained in step 1 at high temperature to obtain ZIF-8 derived porous carbon ZDC ; Step 3: Evenly load lead nanoparticles in the ZDC pores to obtain Pb@ZDC powder; Step 4: Construct a self-healing layer on the surface of the Pb@ZDC electrode; Step 5: Modify the positive electrode active material PbO2 by graphene quantum dots GQDs; Step 6: Add PbO2, GQDs and short fibers into a ball mill and mill them to make the GQDs evenly dispersed on the surface of the PbO2 particles; Add dilute sulfuric acid to make a slurry and stir to form a positive electrode lead paste; Step 7: Apply the lead paste to the lead-calcium alloy grid and cure it at constant temperature and humidity to obtain a GQDs-modified positive electrode plate.
[0014] Preferably, in step 1, the molar ratio of the materials is as follows: a molar ratio of the metal salt Zn⁺ to the ligand 2-methylimidazole of 1:8; zinc nitrate (Zn(NO₃)₂・6H₂O): 1 mol; 2-methylimidazole (C₄H₆N₂): 8 mol; and methanol (CH₃OH): 20,000 mL / mol, calculated per mole of Zn⁺. Step 1 comprises the following steps: Step 11: dissolving zinc nitrate in 100 mL of methanol and magnetically stirring until completely dissolved; Step 12: dissolving 2-methylimidazole in 100 mL of methanol and stirring until dissolved; Step 13: pouring the zinc nitrate solution into the 2-methylimidazole solution and reacting at room temperature for 24 hours; Step 14: After the reaction, collecting the white precipitate by centrifugation, washing it with methanol three times (100 mL each time), and drying it under vacuum at 60°C for 12 hours to obtain ZIF-8 powder.
[0015] Preferably, step 2 further includes: step 21: spreading ZIF-8 powder on a quartz boat with a powder thickness of ≤2 mm, and placing it in the constant temperature zone of a tube furnace; step 22: introducing 99.999% purity nitrogen for 30 minutes at a flow rate of 1000 mL / min, and excluding air; step 23: heating to 1000°C at 5°C / min, keeping warm for 3 hours, and adjusting the nitrogen flow rate to 500 mL / min; step 24: naturally cooling to room temperature, continuously introducing nitrogen for protection, to obtain ZIF-8 derived porous carbon ZDC; step 25: soaking in 1M hydrochloric acid HCl for 24 hours to dissolve the zinc element, washing with deionized water to pH = 7, and vacuum drying at 60°C for 12 hours.
[0016] Preferably, step 3 further includes: step 31: ultrasonically dispersing the ZDC powder in deionized water to form a uniform suspension with a solid-liquid ratio of 1:50; step 32: heating the ZDC suspension to 60°C in a water bath, and adding the chemical plating solution while stirring; step 33: maintaining a constant temperature of 60°C and continuously stirring for 2 hours, and Pb²⁺ is reduced to lead nanoparticles by formaldehyde on the surface of ZDC; step 34: after the reaction is completed, centrifuging at 10,000 rpm for 15 minutes to collect the solid, washing it with deionized water three times, 200 mL each time, and vacuum drying it at 60°C for 12 hours to obtain Pb@ZDC powder.
[0017] More preferably, step 4 is: mixing Pb@ZDC powder and microcapsules in a mass ratio of 10:1, adding deionized water with a solid-liquid ratio of 1:20, and ultrasonically dispersing at 100W for 20 minutes to form a uniform slurry; passing the slurry through a spray dryer with an inlet air temperature of 120°C, an outlet air temperature of 80°C, and a flow rate of 5mL / min to form a 5-10μm thick self-repairing layer on the surface of Pb@ZDC; in step 5, the raw materials for the preparation of graphene quantum dots GQDs include: graphene oxide G O, flake diameter 1-5 μm, oxygen-containing functional group content 30%; step 5 is: GO is dispersed in deionized water with a concentration of 1 mg / mL, ultrasonically exfoliated at a power of 300 W for 2 hours to obtain a single-layer graphene oxide solution; 30% hydrogen peroxide H2O2 solution is added at a volume ratio of 1:10, and refluxed at 100°C for 6 hours to oxidatively cut GO into GQDs with a particle size of 5-10 nm; impurities are removed by dialysis for 24 hours with a molecular weight cutoff of 1000 Da, and GQDs powder is obtained by freeze-drying.
[0018] Without limitation, in step 6, the raw materials selected are as follows: PbO2 active material: 96.52%, graphene quantum dots 2.99%, short fibers: 0.5%, and the above ratios are mass ratios; in step 6, PbO2, GQDs and short fibers are added to a ball mill; the ball milling speed is 300 rpm for 2 hours to uniformly disperse the GQDs on the surface of the PbO2 particles; dilute sulfuric acid with a density of 1.25 g / cm³ is added to prepare the slurry, the solid-liquid ratio is 1:0.3, and the mixture is stirred for 1 hour to form a positive lead paste; in step 7, the lead paste is applied to a lead-calcium alloy grid, and the cured product is cured at a constant temperature and humidity of 60°C, a humidity of 90%, and a time of 24 hours to obtain a GQDs-modified positive electrode plate.
[0019] The present invention also provides a GQDs-modified positive electrode plate prepared according to the above method. The positive electrode plate is a multi-layer composite structure. The positive electrode plate can be divided into a grid support layer from the outside to the inside with a thickness of 0.1-5 mm. The main component material of the grid support layer is 98.72% lead Pb, 0.08% strengthening element calcium, and 1.2% corrosion resistance and bonding strength enhancing element tin Sn; the above ratios are mass ratios, the grid support layer has a mesh structure, the surface is roughened, and the roughness Ra=10-20 μm; the active material layer is coated on both sides of the grid with a thickness of 1.5-2.0 mm; the active material layer is composed of the following substances: 95.0%~97.0% PbO2 as the main body, 2.5%~3.0% GQDs, 0.3%~0.5% short fibers and additives are evenly dispersed; the porosity of the active material layer is 45-50%.
[0020] The positive electrode plate has the following microstructure: GQDs coating structure of PbO2 particles, PbO2 particle size: 1-5μm; GQDs distribution: GQDs with a particle size of 5-10nm are evenly coated on the surface of PbO2 particles, forming a continuous film with a thickness of about 2-5nm; the carboxyl (-COOH) and hydroxyl (-OH) groups on the edge of GQDs are combined with the hydroxyl (Pb-OH) groups on the surface of PbO2 through hydrogen bonds (OH...O); the π conjugated structure of GQDs and the Pb 4 The ⁺ orbitals form π-d bonds; the glass fibers are 5 μm in diameter and 0.5 mm in length and are randomly interwoven; the fibers are interspersed between the PbO2 particles, forming a three-dimensional mechanical support network.
[0021] The present invention also provides a temperature control method for a battery comprising the above-mentioned GQDs-modified positive electrode plate, the method comprising the following steps: A flexible thin-film thermocouple is attached to the interface layer between the active material and the grid of the GQD-modified positive electrode to monitor the GQDs-PbO2 interface temperature; an NTC thermistor is implanted in the active material layer at the center of the positive plate to simultaneously monitor the temperature of the core reaction zone of the plate; ≥2 temperature measurement points are arranged on each positive plate; a carbon nanotube (CNT) heating film is embedded between the positive grid and the active material layer; a microchannel liquid cooling plate is installed on the top of the positive plate, and a graphene heat sink is attached to the side of the plate; the heating film and the liquid cooling plate are connected to the temperature control controller outside the battery housing via a flexible circuit; an STM32H7 series chip is used as the main control unit, and an integrated 16-bit ADC module is used to collect temperature data in real time; a built-in LSTM neural network model predicts the temperature of the GQD-modified layer 10 minutes in advance based on historical temperature, charge and discharge current and other data; There are three control modes for temperature control: Mode 1: Low-temperature activation mode. When the temperature of the GQDs modification layer is ≤-10°C, the CNT heating film is started at 100% power to raise the temperature of the GQDs modification layer to above 15°C within 15 minutes. The electrolyte circulation pump is simultaneously turned on at a flow rate of 0.2L / min. Through heat exchange between the heated electrode and the electrolyte, the electrolyte temperature is raised from -20°C to above 5°C. When the temperature of the GQDs modification layer is <25°C, the charging current is limited to ≤0.5C to avoid low-temperature polarization damage to the GQDs-PbO2 interface. After the temperature is ≥25°C, the normal charging current is gradually restored, and the heating power is maintained at 30% to stabilize the electronic conductivity performance. Mode 2: Normal temperature stable mode. When -10°C < the temperature of the GQDs modification layer < 40°C, the active heating / cooling module is turned off, and passive heat dissipation is achieved through the aluminum matrix silicon carbide composite material of the battery case. The temperature difference between the GQDs modification layer and the center of the electrode plate is monitored in real time. If the temperature difference > 3°C, the low-speed circulation of the microchannel liquid cooling plate is started with a flow rate of 0.1 L / min until the temperature difference ≤ 2°C. When the battery SOC ≥ 80%, the charging voltage is fine-tuned from 2.45 V to 2.40 V through the battery management system BMS. Mode 3: High-temperature protection mode. When the temperature of the GQDs modification layer ≥ 40°C, the microchannel liquid cooling plate is started with a flow rate of 1 L / min and the graphene heat sink. The temperature of the GQDs modification layer is reduced below 35°C within 30 min. The depth of discharge is restricted through the battery management system BMS, and SOC ≥ 30%. If the temperature continues to rise to 50°C, the micro pressure sensor of the electrode plate is triggered for monitoring: when the pressure > 0.5 MPa, the temperature is maintained at 25 - 40°C to ensure that the self-repair microcapsules rupture to release SnSO4 and GQDs; at the same time, the charging current is reduced to 0.3C.
[0022] In the application of the present invention, there is also a temperature-controlled lead-carbon battery adopting the battery temperature control method described above.
[0023] The present invention has the following technical effects: Improvement of electrode material performance: Through a specific preparation method of MOFs-derived carbon-supported lead nanoparticles electrode, the interfacial bonding force between the carbon material and the lead active substance is enhanced, enabling lead to be uniformly deposited on the electrode surface, effectively reducing the risk of sulfation and electrode structure collapse, improving the charge-discharge performance and cycle life of the battery. The agglomeration of lead nanoparticles is inhibited, the active sites are increased, the utilization rate of the active substance is improved, the battery capacity attenuation rate is significantly slowed down, and the battery can provide electrical energy stably for a long time. A self-repair layer is successfully constructed on the electrode surface, enhancing the stability of the carbon-lead interface. When the interface is damaged, it can be automatically repaired, further extending the service life of the battery and improving the reliability of the battery.
[0024] Optimization effect of the positive electrode active substance: The positive electrode active substance PbO2 is modified with graphene quantum dots GQDs and uniformly dispersed through processes such as ball milling, optimizing the performance of PbO2, enhancing its synergistic effect with other materials, thereby improving the overall charge-discharge efficiency and energy density of the battery, enabling the battery to store and release electrical energy more efficiently.
[0025] Advantages of the temperature control system: The designed battery temperature control method uses multiple temperature sensors to accurately monitor the temperature of key battery components. Leveraging the STM32H7 series chip and an LSTM neural network model, the system predicts the temperature of the GQD-modified layer in advance, achieving intelligent and precise control of the battery temperature. Three temperature control modes can be flexibly switched based on the actual battery temperature, ensuring optimal battery operation under varying temperature conditions. Rapid activation at low temperatures prevents damage from polarization; maintaining stability at room temperature reduces unnecessary energy consumption; and providing timely protection at high temperatures to prevent degradation and trigger a self-repair mechanism. This not only improves battery performance and safety, but also further extends the battery life. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The present invention provides a flow chart of a method for preparing a lead-carbon battery electrode.
[0027] Figure 2 This is a schematic diagram of the positive electrode plate structure provided by the present invention.
[0028] Figure 3 This is a flow chart of a lead-carbon battery intelligent temperature control method based on GQDs modified positive electrode provided by the present invention. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0030] The following will be combined with the accompanying drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments.
[0031] like Figure 1 As shown, the present invention provides a method for preparing lead-carbon battery electrodes. Through the controlled carbonization of MOFs precursors, a porous carbon material with high specific surface area, regular pore structure, and nitrogen doping is obtained, which is used to load lead nanoparticles and enhance interfacial bonding. The method includes the following steps: Step 1: Precursor preparation (ZIF-8 synthesis).
[0032] Preferably, the molar ratio formula (core ratio) of each material is: The molar ratio of metal salt (Zn²⁺) to ligand (2-methylimidazole) is 1:8; Zinc nitrate (Zn(NO3)2・6H2O): 1 mol; 2-Methylimidazole (C4H6N2): 8 mol; Methanol (CH3OH): 20000mL / mol (based on each mole of Zn²⁺).
[0033] This ratio is the classic ratio for ZIF-8 synthesis, ensuring an excess of ligand to promote MOF crystallization and form a regular rhombic dodecahedron structure; If you need to prepare a small-scale sample of 0.01 mol Zn²⁺ (as in the original recipe), take 1 / 100 of the molar amount: Zn²⁺: 0.01 mol → 2.97 g (0.01 mol) of zinc nitrate 2-Methylimidazole: 0.08 mol → 6.56 g (0.08 mol) Methanol: 200 mL (20,000 mL / mol × 0.01 mol) In industrial production, the following mass ratio formula is adopted: Zinc nitrate: 2-methylimidazole: methanol = 1:2.21:67.34 (mass ratio). This mass ratio facilitates quick mixing by weighing in industrial production (no need to convert moles). For example, to prepare a 100g zinc nitrate sample, 221g 2-methylimidazole and 6734mL methanol are required.
[0034] In a non-limiting embodiment, the raw material formula is: zinc nitrate (Zn(NO3)2·6H2O): 2.97g (0.01mol) 2-Methylimidazole (C4H6N2): 6.56 g (0.08 mol) Methanol (CH3OH): 200 mL (solvent) Synthesis steps: Step 11: Dissolve zinc nitrate in 100 mL of methanol and stir magnetically until completely dissolved (300 rpm, 10 min); Step 12: Dissolve 2-methylimidazole in 100 mL of methanol and stir until dissolved; Step 13: Pour the zinc nitrate solution quickly into the 2-methylimidazole solution and stir vigorously (800 rpm) at room temperature for 24 hours; Step 14: After the reaction, centrifuge (8000 rpm, 10 min) to collect the white precipitate, wash it three times with methanol (100 mL each time), and dry it in a vacuum at 60 °C for 12 h to obtain ZIF-8 powder.
[0035] Step 2: Carbonizing the ZIF-8 powder obtained in step 1 at high temperature. This step further comprises: Step 21: Spread the ZIF-8 powder on a quartz boat (thickness ≤ 2 mm) and place it in the constant temperature zone of a tube furnace; Step 22: introduce nitrogen (purity 99.999%) to exclude air (flow rate 1000 mL / min, 30 min); Step 23: Raise the temperature to 1000°C (target temperature) at a rate of 5°C / min and maintain for 3 h (nitrogen flow rate adjusted to 500 mL / min); Step 24: Cool naturally to room temperature (nitrogen is continuously introduced for protection) to obtain ZIF-8-derived porous carbon (ZDC).
[0036] Step 25: The carbonized ZDC contains residual zinc (Zn²⁺ from ZIF-8). Preferably, the ZDC is soaked in 1 M hydrochloric acid (HCl) for 24 h to dissolve the zinc, washed with deionized water to pH = 7, and dried under vacuum at 60°C for 12 h.
[0037] The obtained ZDC has the following structural characteristics: Specific surface area: 3405m² / g (BET test, N2 adsorption-desorption method); Pore size distribution: concentrated in 1-5nm (average 2.8nm, BJH analysis); Elemental composition: carbon (C) 89.5%, nitrogen (N) 8.2%, oxygen (O) 2.3% (XPS analysis); Micromorphology: The rhombic dodecahedron structure of ZIF-8 is retained (SEM observation), and the interior is composed of interconnected nanopores (TEM observation).
[0038] Step 3: Evenly load lead nanoparticles in the ZDC pores, use the nano-confinement effect to inhibit the growth of lead dendrites, and enhance the carbon-lead interface bonding strength. Preferably, in this step, the chemical plating solution formula is preferably: Main salt: lead nitrate (Pb(NO3)2) 0.1M (providing Pb²⁺); Complexing agent: 0.2M ethylenediaminetetraacetic acid disodium (EDTA-2Na) (prevents Pb²⁺ hydrolysis and stabilizes the plating solution); Reducing agent: formaldehyde (HCHO) 0.05M (reduces Pb²⁺ to elemental Pb); pH regulator: sodium hydroxide (NaOH) solution (adjust pH to 12 to ensure formaldehyde reduction); Deionized water: Make up to 1L (solvent).
[0039] Step 3 further includes: Step 31: Ultrasonic dispersion of ZDC powder in deionized water (power 200 W, time 30 min) to form a uniform suspension (solid-to-liquid ratio 1:50, i.e., 20 g ZDC dispersed in 1000 mL plating solution); Step 32: Heat the ZDC suspension to 60°C (temperature controlled in a water bath) and add the electroless plating solution while stirring (300 rpm); Step 33: Maintain a constant temperature of 60°C and continue stirring for 2 h. Pb²⁺ is reduced to lead nanoparticles by formaldehyde on the ZDC surface (reaction formula: Pb²⁺ + HCHO + 3OH⁻ → Pb↓ + HCOO⁻ + 2H2O). Step 34: After the reaction, the solid was collected by centrifugation (10,000 rpm, 15 min), washed three times with deionized water (200 mL each time), and dried under vacuum at 60°C for 12 h to obtain Pb@ZDC powder.
[0040] The obtained Pb@ZDC has the following structural characteristics: Lead loading: 35-40% (mass fraction, ICP-OES test); Lead particle size: 5-10 nm (TEM observation, high-resolution electron microscopy shows a lattice spacing of 0.28 nm, corresponding to the (111) crystal plane of Pb); Interface bonding: The nitrogen-doped sites of ZDC (e.g., pyridinic nitrogen and pyrrolic nitrogen) form coordination bonds with Pb atoms (XPS shows that the Pb4f peak shifts 0.5 eV toward lower binding energy, demonstrating strong interaction). Confinement effect: The lead particles are completely embedded in the ZDC pores (TEM cross-section shows no surface agglomeration), inhibiting the growth of lead dendrites (TEM observation shows no dendrites after 500 cycles).
[0041] Step 4: Construct a self-healing layer on the surface of the Pb@ZDC electrode. When microcracks appear on the electrode, the microcapsules rupture and release the repair agent (stannous sulfate, graphene quantum dots), repairing the ion / electron conduction pathway in situ.
[0042] The core material formula in this step is: Stannous sulfate (SnSO4): 0.5M (to inhibit the growth of large PbSO4 grains); Graphene quantum dots (GQDs): 0.1 mg / mL (repairs electron conduction pathways); Deionized water: Solvent (pH adjusted to 4-5 to prevent Sn²⁺ hydrolysis).
[0043] The shell material formula is: Urea (CO(NH2)2): 2g; Formaldehyde (HCHO): 3.5g (37% aqueous solution); Deionized water: 50 mL; Emulsifier: Sodium dodecyl sulfate (SDS) 0.1g (to stabilize the emulsion).
[0044] In step 4, the following steps may be further included: Step 41: Preparation of self-repairing microcapsules (urea-formaldehyde resin shell material).
[0045] Step 41: Prepolymer preparation: Add urea and formaldehyde into a beaker, adjust the pH to 8-9 with NaOH, and react in a 60°C water bath with stirring (300 rpm) for 1 h to obtain a transparent urea-formaldehyde prepolymer solution.
[0046] Step 42: Emulsification and embedding: Add the core material solution (50 mL) to the prepolymer solution and emulsify at high shear speed (10,000 rpm, 10 min) to form an oil-in-water emulsion (core material droplet diameter 1-5 μm).
[0047] Step 43: Curing and molding: Adjust the pH of the emulsion to 3-4 with hydrochloric acid, and react in a 50°C water bath with stirring (200 rpm) for 2 hours. The urea-formaldehyde prepolymer is cross-linked and cured on the surface of the droplets to form microcapsules.
[0048] Step 44: Post-treatment: The microcapsules were collected by centrifugation (5000 rpm, 5 min), washed three times with deionized water, and dried under vacuum at 40°C for 12 h to obtain white powder microcapsules (particle size 1-5 μm, wall thickness 200 nm, SEM observation).
[0049] Step 5: Pb@ZDC powder and microcapsules were mixed in a 10:1 mass ratio. Deionized water (solid-to-liquid ratio 1:20) was added, and ultrasonic dispersion was performed (100W, 20 minutes) to form a uniform slurry. The slurry was passed through a spray dryer (inlet air temperature 120°C, outlet air temperature 80°C, flow rate 5 mL / min), forming a 5-10 μm thick self-healing layer on the Pb@ZDC surface (Scanning electron microscopy showed uniform distribution of microcapsules).
[0050] Step 6: Modify the positive electrode active material (PbO2) by graphene quantum dots (GQDs) to enhance electron conduction and inhibit the shedding of active materials.
[0051] Preferably, the raw materials for preparing graphene quantum dots (GQDs) (using graphene oxide as a precursor) include: graphene oxide (GO, sheet diameter 1-5 μm, oxygen functional group content 30%).
[0052] Without limitation, step 6 is specifically as follows: GO is dispersed in deionized water (concentration 1 mg / mL), ultrasonically exfoliated for 2 h (power 300 W) to obtain a single-layer graphene oxide solution; 30% hydrogen peroxide (H2O2) solution (volume ratio 1:10) is added, refluxed at 100 ° C for 6 h, oxidatively cutting GO into GQDs (particle size 5-10 nm); dialyzed (molecular weight cutoff 1000 Da) for 24 h to remove impurities, and freeze-dried to obtain GQDs powder.
[0053] Step 7: Preparation of positive electrode active material. The following is the raw material ratio form (based on mass fraction or mass ratio) for the preparation of positive electrode active material, which is convenient for scaling production scale according to demand: 1. Mass fraction ratio (most commonly used) Total mass = 100% PbO2 active material: 96.52% (about 97%, simplified expression) Graphene quantum dots (GQDs): 2.99% (about 3%, simplified expression) Short fiber (glass fiber): 0.5% (fixed ratio) Note: Based on the total mass, the proportion of each component is: Example: To prepare 1000g of active material, take 970g of PbO2, 30g of GQDs, and 5g of short fibers.
[0054] 2. Mass Ratio (relative to PbO2): PbO2 active material: 100 parts Graphene quantum dots (GQDs): 3.09 parts (≈3 parts, 3g / 97g) Short fiber (glass fiber): 0.515 parts (≈0.5 parts, 0.5g / 97g) Note: The ratio is: Advantages: It is easy to directly reflect the addition amount of GQDs and short fibers relative to the main material, which is suitable for adjusting the formula during the R&D stage (such as testing the performance when the GQD addition amount is 2% or 4%).
[0055] In an illustrative embodiment, the raw materials used in this step are as follows: 97 g of PbO2 powder (purity 99%), 3 g of GQDs (mass fraction 3%), and 0.5 g of short fibers (glass fibers, diameter 5 μm, length 0.5 mm) (to enhance mechanical strength).
[0056] In step 7, PbO2, GQDs, and short fibers were added to a ball mill (zirconia balls, ball-to-material ratio of 10:1); ball milling was performed for 2 h (300 rpm) to uniformly disperse the GQDs on the surface of the PbO2 particles (SEM showed a GQDs coverage of >90%); dilute sulfuric acid (density 1.25 g / cm³) was added to prepare a slurry (solid-liquid ratio 1:0.3) and stirred for 1 h to form a positive lead paste.
[0057] Step 8: Apply the lead paste to the lead-calcium alloy grid (thickness 2 mm, mesh size 5×5 mm), and cure it at a constant temperature and humidity of 60°C (humidity 90%, time 24 hours) to obtain a GQDs-modified positive electrode plate.
[0058] The key process parameters and control points in the above method are: ; In the above technical solution of the present invention, a high specific surface area (3405m² / g) and nitrogen doping (8.2%) of porous carbon are achieved through controlled carbonization of the ZIF-8 precursor, providing strong anchoring points for lead nanoparticles; the chemical plating process is combined with the nano-confinement effect of the ZDC pores to ensure uniform dispersion of lead particles (5-10nm) and inhibit dendrite growth; urea-formaldehyde resin microcapsules rupture at the cracks in the plate (mechanical stress >1MPa), releasing SnSO4 and GQDs, and in situ repairing the ion / electron conduction pathway; GQDs bind to PbO2 through hydrogen bonds, while improving electronic conduction and active material stability, solving the problem of positive electrode softening.
[0059] like Figure 2 The GQDs-modified positive electrode plate shown above is a multi-layer composite structure, which can be divided into the following layers from the outside to the inside (taking a 2V / 100Ah battery as an example): 1. Grid support layer Material: Lead-calcium alloy (Pb-0.08%Ca-1.2%Sn), thickness 2mm; Structure: Grid design (grid size 5×5mm), surface roughening (roughness Ra=10-20μm) to enhance bonding with lead paste; Function: Provide mechanical support and act as a current collector to conduct electrons.
[0060] 2. Active material layer (lead paste layer) Thickness: 1.5-2.0mm (applied on both sides of the grid); Composition: PbO2 is the main component, with GQDs, short fibers and a small amount of additives (such as sodium lignin sulfonate to inhibit shrinkage) evenly dispersed; preferably, 95.0%~97.0% PbO2 is the main component, with 2.5%~3.0% GQDs, 0.3%~0.5% short fibers and additives evenly dispersed; the porosity of the active material layer is 45-50%.
[0061] Porosity: 45-50% (mercury intrusion testing), ensuring electrolyte penetration and ion migration.
[0062] More preferably, the microscopic components of the positive electrode plate are as follows: ; The above-mentioned positive electrode plate has the following microstructure: (1) GQDs coating structure of PbO2 particles. PbO2 particle size: 1-5μm (after ball milling, the original PbO2 particles are 5-10μm); GQDs distribution: GQDs (particle size 5-10nm) are uniformly coated on the surface of PbO2 particles, forming a continuous film with a thickness of about 2-5nm (TEM observation); Interface binding mechanism: The carboxyl (-COOH) and hydroxyl (-OH) groups on the edge of GQDs are bonded to the hydroxyl (Pb-OH) groups on the surface of PbO2 through hydrogen bonds (OH...O) (XPS shows that the O1s peak has a strong signal at 531.5eV, corresponding to hydrogen bonding); The π-conjugated structure of GQDs and the Pb 4 The ⁺ orbitals form π-d bonding (XPS shows that the C1s peak at 284.6 eV is shifted by 0.3 eV, proving electron transfer).
[0063] (2) Short fiber network reinforcement structure.
[0064] Fiber morphology: The glass fiber has a diameter of 5μm and a length of 0.5mm, and is randomly interwoven (SEM observation). Mechanism of action: The fibers are interspersed between the PbO2 particles to form a three-dimensional mechanical support network (similar to the "reinforced concrete" structure), reducing the shedding rate of PbO2 particles from 15% (no fiber group) to 3% (fiber-added group, vibration test). Porosity regulation: The fibers occupy part of the space, increasing the porosity of the active material layer from 40% (no fiber group) to 45-50%, thereby optimizing electrolyte penetration.
[0065] (3) Pore distribution of active substances.
[0066] Pore type: Macropores (5-20μm): formed by the accumulation of short fibers and PbO2 particles, used for rapid penetration of electrolyte; Mesopores (0.1-5μm): formed by the gap between the GQDs coating and the PbO2 particles, promoting the migration of ions (H⁺, SO4²⁻); Micropores (<0.1μm): nanoscale pores of GQDs themselves (BET test shows that the specific surface area of GQDs is 500m² / g), providing additional reaction interfaces.
[0067] Through experimental structure-performance correlation analysis, it was found that: Positive electrode without GQDs: electron conduction between PbO2 particles depends on point contact (resistivity 0.8Ω·cm); positive electrode with GQDs: the GQDs coating forms a continuous electron conduction network (resistivity 0.2Ω·cm), and the electron migration rate is increased by 4 times (electrochemical impedance spectroscopy EIS test, charge transfer resistance dropped from 120Ω to 30Ω).
[0068] Group without GQDs: After 100 cycles, cracks appeared on the PbO2 particles due to volume expansion (the volume of PbO2→PbSO4 increased by 1.6 times during discharge), and the active material shedding rate was 15%; Group modified with GQDs: GQDs enhanced the binding force between particles through hydrogen bonds and π-d bonds, and the shedding rate was only 3% after 1000 cycles (SEM observation showed that the particles remained intact).
[0069] The high specific surface area of GQDs (500m² / g) can adsorb SO4²⁻ in the electrolyte (adsorption amount 0.2mmol / g, ICP test), reducing the formation rate of large PbSO4 grains (XRD shows that the PbSO4 grain size drops from 50nm to 20nm); sulfate adsorption reduces the local high concentration area on the surface of the electrode and suppresses concentration polarization (the voltage platform during discharge drops from 1.9V to 1.85V, and the group without GQDs drops to 1.7V).
[0070] That is to say, the structure and composition of the positive electrode plate made by GQDs modification and short fiber reinforcement process have the following characteristics: Composition: PbO2 as the main component (97%), with 3% GQDs and 0.5% short fibers evenly dispersed; Microstructure: GQDs coat PbO2 particles through hydrogen bonds and π-d bonds to form an electron conduction network; short fibers are interspersed to form mechanical support; and the hierarchical distribution of pores (macroporous-mesoporous-microporous) optimizes ion migration. Performance advantages: The electron conduction rate is increased by 4 times, the active material shedding rate is reduced by 80%, and the cycle life is significantly extended (the capacity retention rate is 82% after 4500 cycles under HRPSoC conditions).
[0071] This structural design effectively solves the problems of traditional lead-carbon battery positive electrode softening, poor electron conduction, and short deep cycle life through component synergy and microstructure optimization. It is a key technological breakthrough in improving the performance of lead-carbon batteries.
[0072] On this basis, a smart temperature control method for lead-carbon batteries based on GQDs-modified positive electrodes was developed. This method achieves efficient and stable operation of lead-carbon batteries in a wide temperature range by precisely controlling the temperature of the GQDs-modified positive electrodes. Figure 3 As shown, the method includes the following steps: Step A: Constructing a dedicated intelligent temperature control system for GQDs-modified positive electrodes. Step A further comprises the following steps: Install a temperature sensing module. Affix a flexible thin-film thermocouple (accuracy ±0.5°C, thickness 0.1 mm) to the interface layer the interface layer between the active material modified with GQDs and the grid of the positive electrode to monitor the temperature of the GQDs-PbO₂ interface; implant an NTC thermistor in the active material layer at the center of the positive electrode plate (depth 1 mm) to synchronously monitor the temperature of the core reaction area of the electrode plate; arrange ≥2 temperature measurement points on each positive electrode plate to ensure capturing the temperature gradient in the GQDs area (target temperature difference ≤3°C).[[ID=~1]] [[ID=~2]]
[0073] Integrate a thermal management execution module. Embed a carbon nanotube (CNT) heating film (thickness 0.2 mm, power density 300 W / m²) between the grid and the active material layer of the positive electrode to achieve directional heating of the GQDs modified layer; install a microchannel liquid cooling plate (channel width 1 mm) on the top of the positive electrode plate, and attach a graphene heat sink (thermal conductivity 5300 W / (m·K)) to the side of the electrode plate to construct a "liquid cooling + passive heat dissipation" composite heat dissipation system; connect the heating film and the liquid cooling plate to the temperature control controller outside the battery case through a flexible circuit.[[ID=~4]] [[ID=~5]]
[0074] Deploy a core control unit. Use an STM32H7 series chip as the main control unit, integrate a 16-bit ADC module to collect temperature data in real time; build an LSTM neural network model to predict the temperature of the GQDs modified layer 10 minutes in advance (prediction error <0.5°C) based on historical temperature, charge and discharge current and other data.[[ID=~7]] [[ID=~8]]
[0075] Step B: Implement a multi-mode intelligent temperature control strategy.[[ID=~10]] [[ID=~11]]
[0076] The said Step B is divided into the following three control modes according to the temperature sensitivity of the GQDs modified positive electrode:[[ID=~13]] Mode 1: Low-temperature activation mode (GQDs modified layer temperature ≤ -10°C)[[ID=~15]] Directional heating and electrolyte viscosity reduction in coordination. Start the CNT heating film (power 100%), raise the temperature of the GQDs modified layer above 15°C within 15 minutes (at this time, the electron mobility of GQDs returns to 80% of room temperature); synchronously start the electrolyte circulation pump (flow rate 0.2 L / min), and through the heat exchange between the heated electrode plate and the electrolyte, raise the temperature of the electrolyte from -20°C to above 5°C (viscosity drops below 2 mPa·s).[[ID=~17]] [[ID=~18]]
[0077] Linkage of charging strategy. When the temperature of the GQDs modified layer <25°C, limit the charging current ≤0.5C to avoid low-temperature polarization damage to the GQDs-PbO₂ interface; after the temperature reaches the standard (≥25°C), gradually restore the normal charging current (maximum 2C), and maintain the heating power at 30% to stabilize the electron conduction performance.[[ID=~20]] [[ID=~21]]
[0078] Normal temperature stable mode (-10°C < GQDs modified layer temperature < 40°C) [[ID=~23]] Passive heat dissipation and temperature differential balance. The active heating / heat dissipation module is turned off, and passive heat dissipation is achieved through the aluminum-based silicon carbide composite material of the battery housing. The temperature difference between the GQD-modified layer and the center of the plate is monitored in real time. If the temperature difference is greater than 3°C, a low-speed circulation (0.1 L / min) of the microchannel liquid cooling plate is activated until the temperature difference is ≤ 2°C.
[0079] Interface protection strategy: When the battery SOC is ≥80%, the charging voltage is fine-tuned from 2.45V to 2.40V via the BMS to inhibit oxygen evolution on the GQDs surface (reducing oxygen evolution by 40%) and extend the life of the interface layer.
[0080] Mode 3: High temperature protection mode (GQDs modification layer temperature ≥ 40°C).
[0081] Rapid heat dissipation and depth of discharge limitation. Immediately activate the microchannel liquid cooling plate (flow rate 1L / min) and graphene heat sink to reduce the temperature of the GQD modified layer to below 35°C within 30 minutes. Use the battery management system to limit the depth of discharge (SOC ≥ 30%) to prevent excessive conversion of PbO2 to PbSO4, which would cause volume expansion stress and damage to the GQD interface.
[0082] Self-repair triggers synergy. If the temperature continues to rise to 50°C, the plate micro-pressure sensor is triggered. When the pressure exceeds 0.5MPa (indicating microcracks), the temperature is maintained at 25-40°C (the optimal reaction temperature for the repair agent) to ensure that the self-repairing microcapsules rupture and release SnSO4 and GQDs. The charging current is simultaneously reduced to 0.3C to provide a stable environment for the repair reaction (repair efficiency is increased by 35%).
[0083] Step C: Deep data collaboration with the battery management system (BMS).
[0084] Step C includes: the temperature control system shares data such as the temperature of the GQDs modification layer and the viscosity of the electrolyte to the BMS in real time, and the BMS dynamically adjusts the charging and discharging strategy (such as starting heat dissipation 30 minutes in advance during fast charging); receives the SOC and SOH data from the BMS, and optimizes the temperature control threshold based on the battery health status (such as when SOH < 80%, the high-temperature protection start temperature is reduced from 40°C to 38°C), forming a closed-loop control of "temperature-electrical performance-material status".
[0085] Step D: Safety Redundancy and Energy Consumption Optimization. Step D includes: A PTC self-limiting element is built into the CNT heating film. When the temperature exceeds 60°C, the heating power is automatically cut off to prevent overheating of the GQDs-PbO2 interface (hydrogen bond dissociation temperature ≥ 60°C). The heat dissipation system utilizes a hierarchical control strategy, achieving energy consumption of ≤ 1.8% of the total battery energy at room temperature, saving over 50% compared to traditional temperature control solutions.
[0086] The present invention solves the problems of decreased GQDs electron conduction efficiency at low temperatures and insufficient interface stability at high temperatures through directional temperature sensing, precise thermal management execution, and multi-strategy coordinated control of the GQDs-modified cathode, achieving: -40℃ discharge capacity retention rate ≥90%, 60℃ cycle 500 times capacity attenuation ≤9%; The GQDs-PbO2 interface resistance is reduced by 70% compared with the solution without temperature control, and the triggering efficiency of self-healing microcapsules is increased to 95%; The system energy consumption is as low as 1.8% of the total battery energy, significantly expanding the application scenarios of lead-carbon batteries in extreme environments.
[0087] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the invention can be embodied in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as illustrative and non-restrictive, and the scope of the invention is defined by the appended claims, not the foregoing description, and all variations within the meaning and range of equivalents of the claims are intended to be included therein. Any reference sign in a claim should not be construed as limiting the claim to which it relates.
[0088] In addition, it should be understood that although this specification is described in terms of implementation methods, not every implementation method contains only one independent technical solution. This narrative method of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment can also be appropriately combined to form other implementation methods that can be understood by those skilled in the art.
Claims
1. A method for preparing a lead-carbon battery electrode, comprising the following steps: Step 1: Precursor preparation: Dissolve zinc nitrate in methanol and stir magnetically until completely dissolved; dissolve 2-methylimidazole in methanol and stir until dissolved; pour the zinc nitrate solution into the 2-methylimidazole solution and stir at room temperature to react. After the reaction is complete, collect the white precipitate by centrifugation, wash, and vacuum dry to obtain ZIF-8 powder; Step 2: Carbonizing the ZIF-8 powder obtained in step 1 at high temperature to obtain ZIF-8 derived porous carbon ZDC; Step 3: Uniformly load lead nanoparticles in the ZDC pores to obtain Pb@ZDC powder; Step 4: construct a self-healing layer on the surface of the Pb@ZDC electrode; Step 5: Modify the positive electrode active material PbO2 by graphene quantum dots GQDs; Step 6: Add PbO2, GQDs and short fibers to a ball mill and mill until the GQDs are evenly dispersed on the surface of the PbO2 particles; add dilute sulfuric acid to prepare the slurry and stir to form a positive lead paste; Step 7: Apply the lead paste to the lead-calcium alloy grid and cure it at constant temperature and humidity to obtain a GQDs-modified positive electrode plate.
2. The method for preparing a lead-carbon battery electrode according to claim 1, wherein: In step 1, the molar ratio of the materials is as follows: the molar ratio of the metal salt Zn²⁺ to the ligand 2-methylimidazole is 1:8; zinc nitrate Zn(NO³)²・6H²O: 1 mol; 2-methylimidazole C₄H₆N₂: 8 mol; methanol CH₃OH: 20,000 mL / mol, calculated per mole of Zn²⁺; The step 1 comprises: Step 11: Dissolve zinc nitrate in 100 mL of methanol and stir magnetically until completely dissolved; Step 12: Dissolve 2-methylimidazole in 100 mL of methanol and stir until dissolved; Step 13: Pour the zinc nitrate solution into the 2-methylimidazole solution and react at room temperature for 24 hours; Step 14: After the reaction is completed, the white precipitate is collected by centrifugation, washed with methanol three times, 100 mL each time, and dried in vacuo at 60°C for 12 h to obtain ZIF-8 powder.
3. The method for preparing a lead-carbon battery electrode according to claim 2, wherein: Step 2 further includes: Step 21: Spread the ZIF-8 powder on a quartz boat with a thickness of ≤2 mm and place it in the constant temperature zone of a tube furnace; Step 22: introduce 99.999% pure nitrogen gas for 30 min at a flow rate of 1000 mL / min, excluding air; Step 23: Raise the temperature to 1000°C at 5°C / min and hold for 3 h. Adjust the nitrogen flow rate to 500 mL / min. Step 24: Cool naturally to room temperature, and continue to introduce nitrogen for protection to obtain ZIF-8-derived porous carbon ZDC; Step 25: Soak in 1M hydrochloric acid HCl for 24 hours to dissolve the zinc, wash with deionized water to pH = 7, and vacuum dry at 60°C for 12 hours.
4. The method for preparing a lead-carbon battery electrode according to claim 3, wherein: Step 3 further includes: Step 31: Ultrasonic dispersion of ZDC powder in deionized water to form a uniform suspension with a solid-liquid ratio of 1:50; Step 32: Heat the ZDC suspension to 60°C in a water bath, and add the chemical plating solution while stirring; Step 33: Maintain a constant temperature of 60°C and continue stirring for 2 h. Pb²⁺ is reduced to lead nanoparticles by formaldehyde on the ZDC surface. Step 34: After the reaction is completed, the solid is collected by centrifugation at 10,000 rpm for 15 min, washed three times with deionized water (200 mL each time), and dried under vacuum at 60°C for 12 h to obtain Pb@ZDC powder.
5. The method for preparing a lead-carbon battery electrode according to claim 4, wherein: Step 4 is: Pb@ZDC powder and microcapsules were mixed at a mass ratio of 10:1, deionized water with a solid-liquid ratio of 1:20 was added, and ultrasonic dispersion was performed at 100W for 20 minutes to form a uniform slurry. The slurry was passed through a spray dryer with an inlet air temperature of 120°C, an outlet air temperature of 80°C, and a flow rate of 5mL / min to form a 5-10μm thick self-healing layer on the surface of Pb@ZDC. In step 5, the raw materials for preparing graphene quantum dots GQDs include: graphene oxide GO, with a sheet diameter of 1-5 μm and an oxygen-containing functional group content of 30%; step 5 is: dispersing GO in deionized water with a concentration of 1 mg / mL, ultrasonically exfoliating at a power of 300 W for 2 hours to obtain a single-layer graphene oxide solution; adding 30% hydrogen peroxide H2O2 solution, with a volume ratio of 1:10, reflux at 100°C for 6 hours, oxidatively cutting GO into GQDs with a particle size of 5-10 nm; dialyzing with a molecular weight cutoff of 1000 Da for 24 hours to remove impurities, and freeze-drying to obtain GQDs powder.
6. The method for preparing a lead-carbon battery electrode according to claim 5, wherein: In step 6, the raw materials selected are as follows: PbO2 active material: 96.52%, graphene quantum dots 2.99%, short fibers: 0.5%, and the above ratios are mass ratios; in step 6, PbO2, GQDs, and short fibers are added to a ball mill; the ball milling speed is 300 rpm for 2 hours to uniformly disperse the GQDs on the surface of the PbO2 particles; dilute sulfuric acid with a density of 1.25 g / cm³ is added to prepare a slurry with a solid-liquid ratio of 1:0.3, and the mixture is stirred for 1 hour to form a positive electrode lead paste; In step 7, the lead paste is applied to the lead-calcium alloy grid and cured at a constant temperature and humidity of 60° C., a humidity of 90%, and a time of 24 h to obtain a GQDs-modified positive electrode plate.
7. A positive electrode plate made according to claim 6, wherein the positive electrode plate is a multi-layer composite structure, characterized in that: The positive electrode plate can be divided into a grid support layer from the outside to the inside, with a thickness of 0.1-5mm. The main components of the grid support layer are 98.72% lead (Pb), 0.08% strengthening element calcium, and 1.2% corrosion resistance and bonding strength enhancing element Sn. The above ratios are weight ratios. The grid support layer has a mesh structure and the surface is roughened with a roughness of Ra = 10-20μm. The active material layer is coated on both sides of the grid and has a thickness of 1.5-2.0mm. The active material layer is composed of the following substances: 95.0%~97.0% PbO2 as the main component, 2.5%~3.0% GQDs, 0.3%~0.5% short fibers and additives are evenly dispersed; the porosity of the active material layer is 45-50%.
8. A positive electrode plate according to claim 7, characterized in that: The positive electrode plate has the following microstructure: GQDs coating structure of PbO2 particles, PbO2 particle size: 1-5μm; GQDs distribution: GQDs with a particle size of 5-10nm are evenly coated on the surface of PbO2 particles, forming a continuous film with a thickness of about 2-5nm; the carboxyl (-COOH) and hydroxyl (-OH) groups on the edge of GQDs are combined with the hydroxyl (Pb-OH) groups on the surface of PbO2 through hydrogen bonds (OH...O); the π conjugated structure of GQDs and the Pb 4 The ⁺ orbitals form π-d bonds; the glass fibers are 5 μm in diameter and 0.5 mm in length and are randomly interwoven; the fibers are interspersed between the PbO2 particles, forming a three-dimensional mechanical support network.
9. A temperature control method for a battery comprising the positive electrode plate according to claim 8, characterized in that: The method comprises the following steps: A flexible thin-film thermocouple is attached to the interface layer between the active material and the grid of the GQDs-modified positive electrode to monitor the GQDs-PbO2 interface temperature. An NTC thermistor is implanted in the active material layer at the center of the positive plate to simultaneously monitor the temperature of the core reaction area of the plate. ≥2 temperature measurement points are arranged on each positive plate. A carbon nanotube CNT heating film is embedded between the positive plate grid and the active material layer; a microchannel liquid cooling plate is installed on the top of the positive electrode plate, and a graphene heat sink is attached to the side of the plate; the heating film and the liquid cooling plate are connected to a temperature control controller outside the battery case through a flexible circuit; An STM32H7 series chip is used as the main control unit, integrating a 16-bit ADC module to collect temperature data in real time; an LSTM neural network model is built in, and based on data such as historical temperature and charge-discharge current, the temperature of the GQDs modification layer is predicted 10 minutes in advance; The temperature control is divided into the following three control modes: Mode 1: Low-temperature activation mode. When the temperature of the GQDs modification layer ≤ -10°C, start the carbon nanotube CNT heating film with a power of 100%, and raise the temperature of the GQDs modification layer above 15°C within 15 minutes; simultaneously start the electrolyte circulation pump with a flow rate of 0.2 L / min, and through the heat exchange between the heated plate and the electrolyte, raise the electrolyte temperature from -20°C to above 5°C; when the temperature of the GQDs modification layer < 25°C, limit the charging current ≤ 0.5C to avoid low-temperature polarization damage to the GQDs-PbO2 interface; after the temperature ≥ 25°C, gradually restore the normal charging current and maintain the heating power at 30% to stabilize the electron conduction performance; Mode 2: Normal-temperature stable mode. When -10°C < the temperature of the GQDs modification layer < 40°C, turn off the active heating / cooling module, and passively dissipate heat through the aluminum matrix silicon carbide composite material of the battery case; continuously monitor the temperature difference between the GQDs modification layer and the center of the plate. If the temperature difference > 3°C, start the low-speed circulation of the microchannel liquid cooling plate with a flow rate of 0.1 L / min until the temperature difference ≤ 2°C; when the battery SOC ≥ 80%, fine-tune the charging voltage from 2.45V to 2.40V through the battery management system BMS; Mode 3: High-temperature protection mode. When the temperature of the GQDs modification layer ≥ 40°C, start the microchannel liquid cooling plate with a flow rate of 1 L / min and the graphene heat sink, and lower the temperature of the GQDs modification layer below 35°C within 30 minutes; limit the discharge depth through the battery management system BMS, SOC ≥ 30%; if the temperature continues to rise to 50°C, trigger the monitoring of the micro pressure sensor on the plate: when the pressure > 0.5MPa, maintain the temperature at 25 - 40°C to ensure that the self-healing microcapsules rupture to release SnSO4 and GQDs; simultaneously reduce the charging current to 0.3C.
10. A temperature-controlled lead-carbon battery using the battery temperature control method as described in claim 9.